2013
DOI: 10.2147/ceor.s48821
|View full text |Cite
|
Sign up to set email alerts
|

Early parenteral nutrition in critically ill patients with short-term relative contraindications to early enteral nutrition: a full economic analysis of a multicenter randomized controlled trial based on US costs

Abstract: PurposeThe provision of early enteral (gut) nutrition to critically ill patients, started within 24 hours of injury or intensive care unit admission, is accepted to improve health outcomes. However, not all patients are able to receive early enteral nutrition. The purpose of the economic analysis presented here was to estimate the cost implications of providing early parenteral (intravenous) nutrition to critically ill patients with short-term relative contraindications to early enteral nutrition.Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 20 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…In the critical care setting, the use of early parenteral nutrition has been well-demonstrated to benefit patients who would otherwise have not received enteral nutrition until day 3 of ICU admission, resulting in reduced mechanical ventilation needs, improved quality of life, and reduced costs (9,10). These findings have recently been confirmed in the CALORIES trial, a large randomized trial that found no significant difference in infectious complications or 30-day mortality between early initiation of parenteral vs. enteral nutrition among the critically ill (22).…”
Section: Discussionmentioning
confidence: 99%
“…In the critical care setting, the use of early parenteral nutrition has been well-demonstrated to benefit patients who would otherwise have not received enteral nutrition until day 3 of ICU admission, resulting in reduced mechanical ventilation needs, improved quality of life, and reduced costs (9,10). These findings have recently been confirmed in the CALORIES trial, a large randomized trial that found no significant difference in infectious complications or 30-day mortality between early initiation of parenteral vs. enteral nutrition among the critically ill (22).…”
Section: Discussionmentioning
confidence: 99%
“…And fi nally, there was a statistically signifi cant difference in perceived quality of life at 60 days by early PN, but the difference was so small that it was judged clinically meaningless by the investigators. The authors also published a model based health economy analysis in order to predict possible cost reductions with early PN based on the estimated clinical effect size [ 21 ]. In this model, early PN initiation generated a significant reduction of healthcare costs.…”
Section: Results From Recent Rcts Studying the Time Of Pn Initiation mentioning
confidence: 99%
“…There was no clear benefi t of the intervention in the Early PN trial [ 21 ]. There was an increased incidence and hampered recovery of ICU acquired muscle weakness in the EPaNIC trial [ 31 ].…”
Section: Why Early Pn Has Failed To Attenuate Muscle Wasting and Funcmentioning
confidence: 99%
“…34 Finally, increased awareness of catheter-related bloodstream infections, and the requirement to report such infections, 35 could heighten awareness of the risks of parenteral nutrition and deter use.…”
Section: Discussionmentioning
confidence: 99%